Outcomes of patients with metastatic gastrointestinal stromal tumors (GIST) treated with multi-kinase inhibitors other than imatinib as first-line treatment. Issue 6 (27th November 2020) - Boilève, Alice; Dufresne, Armelle; Chamseddine, Ali; Nassif, Elise; Dumont, Sarah; Brahmi, Medhi; Adam, Julien; Rouleau, Etienne; Karanian, Marie; Haddad, Véronique; Faron, Matthieu; Honoré, Charles; et al.
Abstract : Background: Imatinib is the standard first-line therapy in metastatic gastrointestinal stromal tumours (GIST). Investigational multi-kinase inhibitors (MKIs) such as nilotinib, dasatinib or masitinib have been tested as first-line therapies in phase II/III studies. This might theoretically result either in increased survival or in early emergence of resistance to approved MKIs. Methods: To assess whether using MKIs other than imatinib in first line decreases imatinib efficacy in second line for patients with GIST, a retrospective chart review was performed from 2005 to 2011 in two French tertiary centres of patients with GIST who received investigational MKIs (in phase II/III trials) as first-line treatment, followed by imatinib as second line. Results: Of 46 patients, (55% women, median age 55 years (range 24–81)), 22 (47%) had a KIT exon 11 mutation, 1 a KIT exon 9 mutation (2%), 1 a PDGFRA D842V mutation (2%). Out of 46 patients, 21 (46%) received masitinib, 17 (37%) received dasatinib and 8 (17%) received nilotinib as first-line treatment with a median progression-free survival of 18.0 months (95% CI: 8.5 to 25.5). Median time to imatinib failure was 19.7 months (95% CI: 13.5 to 29.0). Median time to second relapse was 48.7 months (95% CI: 31.2 to 72.0). Median overall survival from time of initial metastasis diagnosis was 5.7 years (95% CI: 4.5 to 7.4). Conclusions: Patients with GIST who received investigational MKIs as first-line treatment and imatinib as second line had a time to second relapse longer than that observed historically with imatinib in first line, suggesting that using MKIs other than imatinib in first line does not decrease the efficacy of subsequent treatment lines.